Study of the Assimilation of Diphthongs in Bahasa through the Perspective of Optimality Theory - Sukri, Chintia Dewi; Nasution, Anggita Bella Afrilla (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2024)
This study examines the phonetic changes that occur in the Indonesian language among Indonesian speakers. The aim of this study is to provide a comprehensive analysis of Bahasa using the framework of Optimality Theory. The primary objective of this study is to provide a comprehensive description of the facts and give a theoretical framework for the alteration of phonemes in Bahasa. Additionally, it aims to examine how native speakers pronounce and utilise these phonemes in communication. Phonemic intervention gives rise to various issues, such as assimilation. One potential way to address this issue is the use of Optimality Theory. This study focuses on analysing the diphthong /ai/ in Bahasa Indonesia and its interaction with other phonemes using the framework of Optimality Theory. The study of optimality theory and assimilation in diphthongs enhances our comprehension in specific words of Bahasa Indonesia phonology. Additionally, evidence highlights the significant presence of implicit figures in recent advancements in Optimality Theory.